2017
DOI: 10.18679/cn11-6030/r.2017.021
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescein sodium use during spinal ependymoma resection

Abstract: KEYWORDS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Sun et al reported that SF could help in detecting areas of pathological neoangiogenesis during surgery, for example in tumor infiltration and metastasis. However, it requires a combination of white and yellow light for detection of the areas of the tumor that are not visible with SF [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al reported that SF could help in detecting areas of pathological neoangiogenesis during surgery, for example in tumor infiltration and metastasis. However, it requires a combination of white and yellow light for detection of the areas of the tumor that are not visible with SF [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, It is clearly pointed out in China's 11th Five-Year Plan that "scarce resources should be rationally utilized, strategic reserve resources and precious resources should be protected, and wastes with potential for resource utilization should be comprehensively recycled [4] . In recent years, studies on the extraction of highvalue elements from fly ash have gradually increased [5]- [6] , and breakthroughs have been made in the extraction of aluminum, lithium, gallium and other elements [7]- [8] . Many scholars have also carried out a lot of studies on the extraction of rare earth from coal and fly ash.…”
mentioning
confidence: 99%